Prostorske podobe v obrednih praksah starozaveznih očakov in njihov pomen za razumevanje krščanskega sakralnega prostora = Spatial Images in the Ritual Praxis of the Old Testament Patriarchs and Their Significance for Understanding of the Christian Sacral Space - Debevec, Leon (Edinost in dialog, 2020)
The core problem of the present research are spatial images which appear in the Old Testament descriptions of ritual acts of the patriarchs Abraham, Isac, and Jacob. According to typology they represent a recognizable whole placed between biblical descriptions of the flood and Jahve’s instructions for building the tent of his dwelling. After man’s expulsion from Eden, these ritual acts can be understood as his attempt to re-establish friendship with Transcendence. With the use of literary, archetypical, and comparative analysis we want to present relationship between considered spatial images and attempts of Christianity (as a new religion) to find its own ritual space.